CONSULTATIVE SELLING TECHNIQUES AND COACHING FOR REAL ESTATE BROKERS: APPLYING NLP AND LEADERSHIP TOOLS TO ENHANCE TEAM PERFORMANCE - de Borja Dias , Ricardo Garcez (LUMEN ET VIRTUS, 2024)
The real estate industry has increasingly recognized the importance of consultative selling and coaching methodologies in improving the performance of sales teams. This article examines how certified techniques in consultative sales, coaching, and neurolinguistic programming (NLP) can be applied to strengthen the skills of real estate brokers. It explores the integration of leadership tools, coaching frameworks, and psychological approaches to develop brokers’ emotional intelligence, negotiation ability, and client relationship management. By analyzing academic literature and practical applications, the study highlights how coaching-driven leadership and consultative selling strategies lead to higher client satisfaction, stronger team cohesion, and improved sales outcomes in real estate organizations.